Radiographic inspection of AISI 420 steel friction welds - Kati, Nida; Çay, Vedat Veli; Ozan, Sermin; Çalıgülu, Uğur; Türkmen, Mustafa (Carl Hanser Verlag, 2018)
In this study, X-ray radiographic tests of AISI 420 steel welded by friction welding were studied. During the welding process, three different rotations, 700, 1000 and 1300, were employed while the other parameters such as friction pressure, friction time, upsetting-pressure and upsetting-duration were unchanged. After the completion of welding process, the welded joints were subjected to radiographic tests by X-raydiffraction. The result of the radiographic tests indicates that by increasing rotation speed the amount of flash and joining properties/performance increases in all samples. The best properties of the AISI 420 martensitic stainless steel joints were observed in samples welded at a rotation speed of 1300 (rpm). It has been determined that in harmony with the definition of welding defects and respective radiographic images, lack of fusion is the most common welding defect. © Carl Hanser Verlag, München Materials Testing.
Keywords: AISI 420; Friction welding; Number of rotations; Radiographic inspection